The Role of Land Deed Maker Officials (PPAT) and the National Land Agency (BPN) in Prevention of Land Mafia - Hamidah Nur’Ainiyah; Widhi Handoko; Achmad Arifullah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to analyze: 1) The role of Land Deed Maker Officials (PPAT) and the National Land Agency (BPN) in preventing land mafia in Tuban Regency. 2) Legal protection for victims of land certificates transferred by the land mafia. The approach method used in this study is an empirical juridical approach. The research specification used is descriptive analytical research. This type of data uses primary and secondary data sourced from interviews and literature studies. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1) The role of Land Deed Making Officials (PPAT) and the National Land Agency (BPN) in preventing land mafia in Tuban Regency was carried out to provide legal certainty and protection for the community. The role of the PPAT is to ensure that the parties who will carry out the sale and purchase transactions, read and sign the deed in front of the parties, check and match documents to the BPN, and act carefully in making the deed. Meanwhile, the role of BPN is to reform human resources, re-examine files from PPAT, accelerate PTSL, socialize electronic certificates. 2). Legal protection for victims of land certificates transferred by the land mafia in a preventive manner is by preventive measures such as forming a task force for eradicating land mafias, increasing the integrity and professionalism of law enforcement officers, BPN and PPAT, increasing cooperation between officers, accelerating certification with the PTSL program, as well as providing strict criminal threats to land mafia perpetrators who are proven to have committed crimes. The repressive protection provided to the victim is in the case of the land mafia related to overlapping certificates, multiple certificates, and others, which can be resolved in several ways, such as mediation between village heads or through a court lawsuit.